2017
DOI: 10.1016/j.neuron.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

RORβ Spinal Interneurons Gate Sensory Transmission during Locomotion to Secure a Fluid Walking Gait

Abstract: Animals depend on sensory feedback from mechanosensory afferents for the dynamic control of movement. This sensory feedback needs to be selectively modulated in a task- and context-dependent manner. Here, we show that inhibitory interneurons (INs) expressing the RORβ orphan nuclear receptor gate sensory feedback to the spinal motor system during walking and are required for the production of a fluid locomotor rhythm. Genetic manipulations that abrogate inhibitory RORβ IN function result in an ataxic gait chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 86 publications
(130 reference statements)
10
123
0
Order By: Relevance
“…Here, inhibition exercises state-dependent control of sensory thresholds, for example suppressing nociceptive transmission during acute stress [23], and prevents sensorimotor reflexes from interfering with stable performance of motor acts such as reaching or locomotion [24,25]. Similarly, prepulse inhibition shares characteristics of both state- and task-dependent sensory gating.…”
Section: Discussionmentioning
confidence: 99%
“…Here, inhibition exercises state-dependent control of sensory thresholds, for example suppressing nociceptive transmission during acute stress [23], and prevents sensorimotor reflexes from interfering with stable performance of motor acts such as reaching or locomotion [24,25]. Similarly, prepulse inhibition shares characteristics of both state- and task-dependent sensory gating.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, last order GABAergic interneurons specifically involved in presynaptic inhibition have been genetically identified in rodent models (Fink et al, 2014;Koch et al, 2017) and presynaptic inhibitory mechanisms were shown to rely not only on GABAergic signaling, but also on other neurotransmitters, neuromodulators and receptors that also could contribute to our results (Kremer & Lev-Tov, 1998;Hochman et al, 2010;Lucas-Osma et al, 2018). Finally, mechanisms other than PAD are also likely to contribute to presynaptic inhibition of Ia afferents and possibly contribute to the PAD-independent presynaptic inhibition of the H-reflex in our experiments (Price et al, 1984;Stuart & Redman, 1992;Hultborn et al, 1996;Curtis et al, 1997;Garcia-Ramirez et al, 2014).…”
Section: Possible Mechanisms Contributing To the Reorganization Of Afmentioning
confidence: 99%
“…The Cre expression pattern has been confirmed and found to faithfully recapitulate the endogenous Rorb expression pattern. [20][21][22] Currently, no suitable Rorb antibody for high-quality immunostaining is available, and thus the use of Rorb-IRES-Cre provides an alternative approach for tracing the Rorb expression pattern. When Rorb-IRES-Cre strain is crossed with the Cre reporter mouse strain Rosa26-CAG-Loxp-stop-Loxp-tdTomato (Ai9; abbreviated as Rosa26-CAG-LSL-tdTomato), 23 most, if not all, cells that express Rorb permanently express tdTomato in the Rorb-IRES-Cre/+; Rosa26-CAG-LSL-tdTomato/+ mice ( Figure 1B).…”
Section: Rorb-ires-cre Is a Highly Suitable Tool For Fate-mapping Amentioning
confidence: 99%
“…[20][21][22] Currently, no suitable Rorb antibody for high-quality immunostaining is available, and thus the use of Rorb-IRES-Cre provides an alternative approach for tracing the Rorb expression pattern. B, Rationale for how tdTomato expression faithfully recapitulates Rorb-IRES-Cre pattern.…”
mentioning
confidence: 99%